Answer:
b = 0
Explanation:
To find the value of b, we will follow the steps below;
Using the distance formula:
D = √(x₂-x₁)² + (y₂-y₁)²
from the question given,
A (-3, b), this implies
(-3, b) = (x₁ ,y₁)
x₁=-3 and y₁ = b
similarly
B (1, 3)
(1, 3) = (x₂,y₂)
this implies
x₂ = 1 and y₂=3
D= 5
we can now proceed to insert the values into the formula and then solve for b
D = √(x₂-x₁)² + (y₂-y₁)²
5 = √(1+3)² + (3-b)²
5 = √4² + (3-b)²
5=√16 + (3-b)²
take the squares of both-side of the equation
5² = 16 + (3-b)²
25 = 16 + (3-b)²
subtract 16 from both-side of the equation
25 - 16 = (3-b)²
9 = (3-b)²
Take the square root of both-side
√9 = 3-b
3 = 3-b
add b to both-side of the equation
3 + b = 3 - b+ b
3 + b = 3
subtract 3 from both-side of the equation
3+b-3 = 3-3
b = 0
Therefore, the value of b is 0